Unusual Fungal Species in Routine Cervicovaginal Papanicolaou Smears - Alexandra Corina Faur; Laura Andreea Ghenciu; Camelia Vidiţa Gurban; Daniela Cornelia Lazăr (IMR Press, 2023)
Background: Conventional cervicovaginal Papanicolaou (Pap) stained smears are a common investigation in gynaecological practice for detecting cancerous and precancerous cervicovaginal lesions, as well as infections and inflammatory processes. Although Candidiasis is the most common fungal infection detected on Pap smears, cytopathologists sometimes also have to deal with the challenge of fungal contaminants. The aim of this study is to present and discuss the findings of two rare fungal organisms in the context of previous literature reports. Methods: Over a period of one year, 4496 smears were submitted to the cytopathology laboratory for analysis. These were sampled from women aged 16-72 years. Slides were processed using the conventional Papanicolaou stain (Pap stain) method. The current available literature was reviewed using relevant key words. Results: Of the 4496 smears examined, the most frequently detected fungal species was Candida species spp. (523 cases), followed by Gardnerella Vaginalis (450 cases) and Trichomonas Vaginalis (50 cases). Also identified were 20 cases with Actinomyces spp. and 18 cases with unusual contaminants belonging to Penicillium and Alternaria spp. A literature search found that five previous articles reported cervical cytology cases with Penicillium and Alternaria spp. Conclusions: Papanicolaou smears are useful for the detection of vaginal microorganisms. Usual pathogenic flora need to be distinguished from contaminants such as Penicillium and Alternaria spp., as observed in this and previous studies.